Effect of nitrogen amendments and inoculum on spent mushroom substrate composting for sustainable waste management - Rathnayake, Rathnayake Mudiyanselage Ayesha Priyadarshani; Gamage, Gallala Gamage Dasun Sandeepa; Amarasinghe, Sajeewani Rajika; Perera, Peliyagodage Chathura Dineth (Ecological Questions, 2026)
Spent Mushroom Substrate (SMS) is the medium used in mushroom cultivation and is mostly dumped into the environment as waste. Composting SMS is identified as a sound method of reuse. However, lower N levels and reduced microorganism activity limit aerobic decomposition. Therefore, this experiment was conducted to evaluate the effects of amending different N sources to obtain good-quality SMS compost. Nitrogen sources were mixed to SMS separately based on the C/N ratio of each source, with and without the bio-dynamic inoculum to obtain ten SMS compost mixtures with Urea (T1), Urea + inoculum (T2), Gliricidia sepium leaves (T3), G. sepium leaves + inoculum (T4), Tithonia diversifolia leaves (T5), T. diversifolia leaves + inoculum (T6), Pueraria phaseoloides leaves (T7), P. phaseoloides leaves + inoculum (T8), SMS without inoculum (T9), and SMS with inoculum (T10). Treatments were arranged in a Completely Randomized Design (CRD) with four replicates and composted for 90 days. Final samples were analyzed for total organic matter (%), total N (%), C/N, total K (%), total P (%), pH and EC and data analysis was done using SAS software 9.1.3. According to the results, T7 and T8 have given a significantly higher level of N% (1.71 and 1.89, respectively). The C/N ratio of all treatments except T5, T9 and T10 reached an average of 20-30, and T8 recorded the lowest. In all treatments EC values were within the Sri Lankan Standards (<4 mS/cm), however, the pH values were higher (>8.5). Based on the results, it is concluded that treating SMS with P. phaseoloides leaves with the bio-dynamic inoculum could obtain good quality SMS compost resembling the given compost standards.